ANALISIS USER EXPERIENCE DAN PERANCANGAN USER INTERFACE WEBSITE KARTU JAKARTA MAHASISWA UNGGUL DENGAN METODE POST STUDY SYSTEM USABILITY QUESTIONNAIRE DAN HEURISTIC EVALUATION - Dina Septina (2023)
Kartu Jakarta Mahasiswa Unggul (KJMU) is a Conditional Cash Transfer (CCT) program initiated by the Jakarta Provincial Government to provide financial assistance for improving the quality of higher education. The P4OP Department utilizes a website to disseminate information related to KJMU. However, until now, information about KJMU is still being disseminated through the KJP website because the establishment of a separate KJMU website has not been implement. Based on the results of the questionnaire distributed by the researchers, it was obtained data that as much as 98.3% (119 respondents) of the 121 questionnaire respondents felt the need to separate the KJP and KJMU websites and improve the interface of the running website. This study aims to assess user experience and redesign the User Interface to achieve optimal usability for the existing KJMU website. The design Thinking approach is employed in this research to obtain solutions that meet user needs. The analysis methods used include questionnaires and inspections using the Post Study System Usability Questionnaire and Heuristic Evaluation from both user and expert perspectives. The research findings demonstrate an improved usability level more than 60% based on PSSUQ questionnaire for the proposed user interface design and prototype compared to the current website, along with a reduction in the number and severity of identified usability issues through heuristic evaluations.